Aninhamento em comunidades: padrões e processos subjacentes - Gomes, Carolina Ramos Caiado (2014)
Nestedness is a particular pattern of species distribution in metacommunities in which a group of species found in poorer sites is a subset of the group of species found in richer sites. In the beta diversity partition context, nestedness is considered one of beta diversity components, jointly with species turnover. However, it is clear now that this term has been used in a wrong way instead of beta diversity due to richness differences. In specific cases that such richness differences reflect an ordered gain or loss of species between sites, then the nested pattern emerges. In the present work I used the beta diversity partition approach, focusing on the richness differences component, combined with a specific metric of nestedness, the NODF, to explore situations in which the richness differences between sites occur in a nested way considering different systems and scales of study. In the first chapter I use aquatic macroinvertebrates communities to show the importance of spatial position of patches of the same microhabitat in generating nestedness in riffles. I found that patches and riffle sites located in the beginning of the riffles are poorer then patches and riffle sites at the end of the same riffles, and that initial sites are nested in final sites in a same riffle. In the second chapter I use birds and mammals communities in the New World to assess how nestedness varies in latitudinal and longitudinal gradients. Nestedness emerged in several regions in both gradients, and it is always related to richness differences in such gradients combined with directional processes that cause an ordered loss or gain of species.